6x-54=-12x+36

Simple and best practice solution for 6x-54=-12x+36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-54=-12x+36 equation:


Simplifying
6x + -54 = -12x + 36

Reorder the terms:
-54 + 6x = -12x + 36

Reorder the terms:
-54 + 6x = 36 + -12x

Solving
-54 + 6x = 36 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-54 + 6x + 12x = 36 + -12x + 12x

Combine like terms: 6x + 12x = 18x
-54 + 18x = 36 + -12x + 12x

Combine like terms: -12x + 12x = 0
-54 + 18x = 36 + 0
-54 + 18x = 36

Add '54' to each side of the equation.
-54 + 54 + 18x = 36 + 54

Combine like terms: -54 + 54 = 0
0 + 18x = 36 + 54
18x = 36 + 54

Combine like terms: 36 + 54 = 90
18x = 90

Divide each side by '18'.
x = 5

Simplifying
x = 5

See similar equations:

| -(x-75)= | | 3(4x+9)=75 | | 5(n-10)-7n=18 | | 2x+64=180 | | 7w^2-25=62 | | 6(3x+11)=3 | | -3x-10=6-2x | | 10x+4-2-3x=-12 | | 27+4y-9=17y-14-5y | | 7n+4=3n-8 | | 36w^2-25=62 | | 4(y+5)-3y+7=10 | | r^2-12r+35=62 | | 17x-32+24x=12 | | 2(n+1)+3(n+6)=-35 | | x=62square | | 3r^2+16r-35= | | 2(2g-3)=24 | | -5+p=-36 | | x(x-5)+(x-5)=0 | | 4=0.6s | | 11x^2-2x+9=62 | | 4n+5-2n+10=49 | | A(n)=4+(n+1)(6) | | z^5=0 | | 15.35+10.25c=425.35 | | -3(4x+3)+4(6x+1)=43+4x | | (149-3x)=(5x+12) | | 1+14i= | | 5n^2-58n+80= | | 2x-6+2x-6+x+3+x+3=26 | | 3(-x-3)=4x-2(x+1) |

Equations solver categories